Identification of the vaccinia virus gene encoding an 18-kilodalton subunit of RNA polymerase and demonstration of a 5' poly(A) leader on its early transcript. - Ahn, B Y (1990)
The DNA-dependent RNA polymerase of vaccinia virus contains 8 to 10 virus-encoded polypeptides. We have mapped the gene encoding an 18-kilodalton RNA polymerase subunit to D7R, the seventh open reading frame of the HindIII D genomic subfragment. Localization of this gene was achieved by using antibody to the purified RNA polymerase for immunoprecipitation of the in vitro translation products of in vivo-synthesized early mRNA selected by hybridization to cloned DNA fragments. The identification was confirmed by translation of D7R transcripts made in vitro with bacteriophage T7 RNA polymerase. The phenotypes of two previously isolated conditionally lethal temperature-sensitive mutants that map to D7R (J. Seto, L. M. Celenza, R. C. Condit, and E. G. Niles, Virology 160:110-119, 1987) are consistent with an essential role of this subunit in late transcription. This polymerase gene, designated rpo18, predicts a polypeptide of 161 amino acids with a molecular mass of 17,892. The rpo18 gene is transcribed early in infection, even though the 5'-TAAATG-3' motif, which is conserved among many genes of the late class, is present near the RNA start site. Characterization of the 5' end of the early transcript by several different methods, including cDNA cloning, revealed a poly(A) leader with up to 14 adenylate residues, whereas only 3 are present in the corresponding location of the DNA template. Similar but somewhat longer poly(A) leaders have previously been observed in mRNAs of late genes. We noted a TAAATG motif near the initiation site of several other early genes, including the viral DNA polymerase, and carried out additional experiments to demonstrate that their early transcripts also have 5' poly(A) leaders. Thus, formation of the poly(A) leader is not exclusively a late function but apparently depends on sequences around the transcription initiation site.